Eksplorasi Sistem Pengendalian Internal Baitul Maal Wat Tamwil di Daerah Istimewa Yogyakarta - Prakosa, Khairul Yoga; Suandi, Aprilia Beta (IAIN Kudus, 2024)
Baitul Maal Wat Tamwil (BMT) is a microfinance institution (LKM) that plays an important role in economic development. BMT faces several operational problems, including weak management, collateral requirements that can be burdensome for the poor, an extreme operational environment because it does not have strict regulations, and the risk of default because it serves MSMEs that have limited regulations. This research aims to understand how BMT management develops an internal control system (SPI) framework and then analyzes supporting and inhibiting aspects in its implementation. This research uses a qualitative method with a case study approach. Primary data is in the form of semi-structured interviews while secondary data is in the form of documents related to SPI. All BMTs have developed the SPI training framework through and encountered operational experience. The four control activities found were cash control, operations, financing, and sharia compliance. The supporting aspect in implementing SPI comes from the encouragement of normative isomorphism. The inhibiting aspect comes from the lack of competency of BMT resources to implement SPI.Keywords: Baitul Maal Wat Tamwil; Microfinance Institution Internal Control System; Institutional Theory